Hemodynamic Effects of Intravenous Ephedrine Administration During General Anesthesia for Radiation Therapy in Cats - Daichi Seki; Seijirow Goya; Kenji Teshima; Yoshiki Yamaya (Veterinary Sciences, 2026)
Ephedrine is used as a vasopressor in cats, but the hemodynamic effects of intravenous (IV) administration have not been characterized. This study evaluated the hemodynamic effects of IV ephedrine in 10 cats that developed hypotension during anesthesia. Cats received either saline (SE) or atropine (AE) before ephedrine for hypotension (mean arterial pressure < 60 mmHg). Hemodynamic variables were analyzed using a linear mixed-effects model. No significant differences were observed between groups in the response rate (defined as mean arterial pressure ≥ 65 mmHg after ephedrine administration; SE, 70%; AE, 80%) or the duration of the pressor response (SE, 4 [1–10] min; AE, 3 [1–5] min). A significant main effect of ephedrine administration was identified for the systemic vascular resistance index, with increases observed in both groups, reaching statistical significance in the AE group. Significant interaction effects were observed for heart rate and cardiac index, both of which increased significantly in the AE group. These findings indicate that the pressor effect of IV ephedrine in anesthetized hypotensive cats is mediated primarily by increasing systemic vascular resistance index. Ephedrine provides a rapid and reliable pressor response and may be considered an early treatment option for anesthesia-induced hypotension in cats.